Dioxygen and Metabolism; Dangerous Liaisons in Cardiac Function and Disease - Angelini, Aude; Pi, Xinchun; Xie, Liang (Frontiers in Physiology, 2017)
The heart must consume a significant amount of energy to sustain its contractile activity. Although the fuel demands are huge, the stock remains very low. Thus, in order to supply its daily needs, the heart must have amazing adaptive abilities, which are dependent on dioxygen availability. However, in myriad cardiovascular diseases, “fuel” depletion and hypoxia are common features, leading cardiomyocytes to favor low-dioxygen-consuming glycolysis rather than oxidation of fatty acids. This metabolic switch makes it challenging to distinguish causes from consequences in cardiac pathologies. Finally, despite the progress achieved in the past few decades, medical treatments have not improved substantially, either. In such a situation, it seems clear that much remains to be learned about cardiac diseases. Therefore, in this review, we will discuss how reconciling dioxygen availability and cardiac metabolic adaptations may contribute to develop full and innovative strategies from bench to bedside.